RANCANGAN ANIMASI PEMBELAJARAN INTERAKTIF ALFABET PADA PENDIDIKAN ANAK USIA DINI - Ahmad Faris; Ade Fitria Lestari (JURNAL TEKNIK KOMPUTER AMIK BSI, 2016)
Abstract – An early age is the golden age for children inreceiving and caught a novelty. From an early age to begiven the knowledge that is beneficial to the development ofthe mindset that would be useful for him and thesurrounding environment. The introduction of the alphabetis learning introduction letters that are the basis for earlychildhood. Teachers in providing an introduction to thealphabet to his disciples is to pronounce each letter of thealphabet and wrote the alphabet on a Blackboard, it provedless effective for pupils in the following and accept theintroduction of the alphabet. Animation serves as a mediumof learning that is interesting because in visual form themove accompanied audio which can be used to explain thedifficult subject matter presented. In facilitating theintroduction of the alphabet in an interesting then designedan interactive animation of the introduction of the alphabetfor the pupils in the OLD. This research uses the method ofcollecting the data of observation, interview, and the study ofthe literature. While the model of development system with awaterfall and applications using Macromedia FlashProfessional 8. The results of this research in the form ofstoryboards, design of state transition diagrams,implementation design and testing with interface blackboxand white box testing. The presence of interactive animatedintroduction to the alphabet is expected to help pupilsunderstand, recognize letters and words with interestinglearning media.Intisari - Usia dini merupakan usia emas bagi anak dalammenerima dan menangkap hal yang baru. Sejak usia diniperlu diberikan pengetahuan yang bermanfaat bagiperkembangan pola pikir yang nantinya bisa bergunauntuk dirinya dan lingkungan di sekitarnya. Pengenalanalfabet adalah pembelajaran pengenalan huruf-hurufyang dasar bagi anak usia dini.Guru dalam memberikan pengenalan alfabet kepadasiswa adalah mengucapkan masing-masing huruf alfabetdan menulis huruf alfabet di papan tulis, cara ini dirasakurang efektif bagi siswa dalam mengikuti dan menerimapengenalan alfabet. Animasi berperan sebagai mediapembelajaran yang menarik karena dalam bentuk visualbergerak disertai audio yang dapat di manfaatkan untukmenjelaskan materi pelajaran yang sulit disampaikan.Dalam memudahkan pengenalan alfabet secara menarikmaka dirancang sebuah animasi interaktif pengenalanalfabet untuk siswa di PAUD. Penelitian ini menggunakanmetode pengumpulan data observasi, wawancara, dansdteundgia np uwsatatekraf.a lSl eddaann gakpalink amsi omdeeln gpgeunngaekmabna nMgaacnr osmisetedmiaFlash Profesional 8. Hasil dari penelitian ini beruparancangan storyboard, state transition diagram,implementasi rancangan antar muka dan pengujiandengan blackbox dan white box testing. Kehadiran animasiinteraktif pengenalan alfabet ini diharapkan dapatmembantu siswa memahami, mengenal huruf dan katadengan media pembelajaran yang menarik.Kata Kunci – Usia Dini, Alfabet, Animasi Interaktif, Flash